The image of the river in Latin/o American literature : written in the water - Murphy, Jeanie; Murphy, Jeanie; Rivero, Elizabeth G.; Rivero, Elizabeth G. (Ecocritical theory and practice., 2018)
Through the lens of ecocriticism, history, memory, and gender studies, this book studies the many ways in which the image of the river has been integrated into Latin/o American literature from the period of exploration and colonization to modern times, examining the imagery and symbolism tied to rivers in the writings of the region.